Multiparticulate formulation of Valdecoxib for the treatment of rheumatoid arthritis - Audity Ganguly Rupesh, Sarasija Suresh, Vinay Pand (Journal of Applied Pharmaceutical Science)
An oral controlled onset dosage form intended to approximate the chronobiology of rheumatoid arthritis was proposed for colonic targeting. The multiparticulate system comprising of non-pareil seeds coated with Eudragit S100 was designed for chronotherapeutic delivery of valdecoxib. The drug was coated onto non-pareil seeds by powder layering technique using the conventional coating pan. Different coat weights of non-aqueous dispersions were applied onto the drug-coated pellets using spray coating technique. In vitro dissolution tests of the coated pellets were performed in different pH media for a period of 11 hours. The in-vitro dissolution tests showed that the release of valdecoxib from the coated pellets depended on the pH of the dissolution fluid and the coat weights applied. All the formulations exhibited no release of drug in the pH 1.2 and pH 4 buffers; drug release took place in phosphate buffer of pH 7.4. Further intactness of the drug in the formulation and the uniformity of the polymer coating were checked by the infrared study and scanning electron microscopy. Stability studies inferred that the drug undergoes no considerable degradation pattern at room temperature and 40oC even after three weeks. All the above results show that the formulation could be highly advantageous in the chronotherapy of rheumatoid arthritis with appreciable drug release and physiochemical properties.
Keywords: Oral controlled onset dosage form,Chronobiology,Eudragit S100,Valdecoxib,Powder layering technique,multiparticulate system.